Serum Cystatin C Trajectory Is a Marker Associated With Diabetic Kidney Disease - Wang, Nana; Lu, Zhenyu; Zhang, Wei; Bai, Yu; Pei, Dongmei; Li, Ling (Frontiers in Endocrinology, 2022)
Objective: To explore the association of trajectory of serum Cystatin C (Cysc) with diabetic kidney disease (DKD), a retrospective cohort study was held in Chinese subjects. Method: A review of 2928 diabetes mellitus (DM) patients admitted to clinic and ward of the Endocrinology Department, Shengjing Hospital of China Medical University from January 1, 2014 to December 31, 2014 was performed. Subsequent visits to the hospital were followed until December 31, 2020. The primary endpoint was the incidence of DKD as diagnosed by urinary albumin/creatinine ratio ≥30 mg/g and/or estimated glomerular filtration rate <60 mL/min per 1.73 m2. Healthy control subjects were identified from a healthy checkup database held in Shengjing Hospital from 2016 to 2019. The latent class growth mixed modeling (LCGMM) method was used to analyze latent classes of serum Cysc in healthy and DM subjects. Finally, the hazard ratios (HRs) of latent classes of Cysc in DM subjects were analyzed by Cox regression analysis. Results: A total of 805 Type 2 diabetes mellitus (T2DM) and 349 healthy subjects were included in the trial. The HRs of quartiles of baseline Cysc in T2DM subjects were 7.15 (95% confidence interval (CI), 2.79 to 25.57), 2.30 (95% CI, 1.25 to 4.24) and 2.05 (95% CI, 1.14 to 3.70), respectively, for quartile 4(Q4), Q3 and Q2 when compared with Q1. By LCGMM, a 1-class linear model was selected for the Cysc latent class in healthy subjects. In contrast, a 3-class linear model was selected for that in DM subjects. The slopes of the three latent classes in T2DM subjects were larger than the slope in healthy subjects. The HRs of incident DKD was 3.43(95% CI, 1.93 to 6.11) for the high-increasing class and 1.80(95% CI, 1.17 to 2.77) for the middle-increasing class after adjusting for confounding variables. Conclusions: Patients with T2DM had a higher velocity of increase in Cysc than healthy subjects. Patients with high baseline Cysc values and high latent increasing velocity of Cysc had a higher risk of developing DKD in the later life. More attention should be paid to patients with these high-risk factors.